Design technology of fusion reactors - Akiyama, M (World Scientific, 1991)
This book contains the contributions of over 40 outstanding applied physicists from Japan specializing in this area of design technology. Among them are K Miya, S Yamamoto, M Ohnishi, Y Ogawa, Y Sakai, T Kuroda, H Nariai, K Miyazaki, H Madarame, M Saitoh. The topics discussed extensively include: Plasma; First Wall and Impurity Control Engineering; Blanket and Shield; Magnet; Heating; Power Supply; Tritium Systems; Fuel Supply System; Remote Handling; Vacuum System; Building; Cooling System; Fundamentals for Design Technology